Gambaran tingkat kepuasan pasien terhadap pelayanan kefarmasian pada era globalisasi di klinik utama “X” Kota Semarang. - FX Sulistiyanto WS; Aloysius Barry Anggoro; Erwin Indriyanti . (VISIKES: Jurnal Kesehatan Masyarakat, 2023)
Pharmaceutical services are the main support in every health facility and are part of health services that aim to increase the rational, safe and efficient use of drugs in order to achieve an increase in the quality of human life. Efforts to improve pharmacy services in the main clinic need to be accompanied by an evaluation of the level of satisfaction. Consumer satisfaction is a response to every service received and is an important part because patient satisfaction cannot be separated from the quality of health services.            The purpose of this study was to determine the characteristics of patients based on gender, age, last education and occupation. Then to determine the level of patient satisfaction with pharmaceutical services.            The method used in this research is descriptive method with a quantitative approach. Data analysis uses percentages and a Likert scale. The population in this study were outpatients who received pharmacy services at the main clinical pharmacy installation "X" Semarang City.            The results of the characteristic study showed that 80% of the respondents were female. Based on the age of the respondents who visited the most were aged 26 - 35 years (33.1%), and the least were aged 56 - 65 years (7.4%). The majority of respondents have high school education (42.3%). Most of the respondents' occupational data in this study were other (60%), dominated by housewives. The frequency of visits (71.4%) of respondents visited more than 2 times and 28.6% of respondents visited 2 times. The average result of patient satisfaction based on five dimensions obtained a value of 3.04 with a satisfied statement. Keywords: Pharmaceutical services, ServQual, satisfaction, primary clinics